(untitled) (Bangladesh Critical Care Journal, 2024)
Fat embolism syndrome is a fatal condition that affects several organs. It often occurs after trauma or orthopedic surgeries. Most are unnoticed, and treatment of it is primarily supportive, with early fracture repair as a preventative measure. This case report describes a patient who had a left tibia fibula fracture diagnosed using Gurd’s criteria and verified by a CT pulmonary angiography and MRI, and was treated with supportive care. Bangladesh Crit Care J September 2024; 12 (2): 167-171